The Role of Health Care Transformation for the Chinese Dream Powering Economic Growth, Promoting a Harmonious Society - Mattke, Soeren (RAND Corporation, 2014)
After having successfully expanded health insurance coverage, China now faces the challenge of building an effective and efficient delivery system to serve its large and aging population. RAND researchers recommend that rather than emulate the models of Western countries, which have well-known limitations, China should create an innovative model based on population health management principles and sophisticated health information technology.